2017
DOI: 10.1007/s41062-017-0053-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using rubber waste fibers as reinforcements for sandy soils

Abstract: In this study, an alternative and environmentally friendly method for the reinforcement of dune sand is proposed. This technique consists of using randomly distributed rubber fibers to improve the engineering properties of sand. Rubber fibers are added to the sand with different percentages: 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75 and 2% of dry weight of sand. The experimental program carried out consists of investigating the effect of rubber fibers on the shear strength properties of sand. Reinforced and unreinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
4
8
0
Order By: Relevance
“…Except for old tires, rubber particle recycled from old garden hoses, plastic shoes and other items can also increase the shear strength of the treated soil [ 70 ]. Specially, short rubber fibers can reduce the displacement rate and improve the ductility of sandy soil [ 71 ]. Moreover, adding waste broken glass powder or waste textile fibers also has positive effect on the strength and deformation performance of soil [ 72 , 73 , 74 ].…”
Section: Unconventional Materials Used In Soil Improvementmentioning
confidence: 99%
“…Except for old tires, rubber particle recycled from old garden hoses, plastic shoes and other items can also increase the shear strength of the treated soil [ 70 ]. Specially, short rubber fibers can reduce the displacement rate and improve the ductility of sandy soil [ 71 ]. Moreover, adding waste broken glass powder or waste textile fibers also has positive effect on the strength and deformation performance of soil [ 72 , 73 , 74 ].…”
Section: Unconventional Materials Used In Soil Improvementmentioning
confidence: 99%
“…The effect of materials such as cement, lime, fly ash, polymers, resins, acids, and ions has been investigated by researchers for years (2). As one of the conventional and most prevalent soil stabilizers, numerous geotechnical researchers have justified cement to hand over many advantages, including higher strength and stiffenss, liquefaction resistance, lifespan increment, and curbing deformations (2,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…This can be beneficially used in settlement reduction and improvement of bearing capacity in shallow foundations design [35]. Meddah and Merzoug [36] evaluated the shear strength properties of sand reinforced with rubber fibers in the dense and loose state with fiber percentages of 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75 and 2% of the sand dry weight. Their results revealed that the rubber fibers use in the dune sand is not only the environmentally friendly method but also it improves the peak strength, residual strengths, and characteristics of shear strength, and makes the mechanical behavior of sand more ductile [36].…”
Section: Introductionmentioning
confidence: 99%